Enhancing productivity of spring maize (Zea mays) with intercrops and row-orientations - Kumar, Jaswinder; Singh, Thakar; Singh, Som Pal (The Indian Journal of Agricultural Sciences, 2020)
A research experiment was conducted on spring maize (Zea mays L.) in a split-plot design with two row orientations in main plots and nine intercropping including sole systems in sub plots during 2016-17 at Punjab Agricultural University, Ludhiana. Row orientation did not significantly influence the growth and yield of spring maize. Spring maize equivalent yield and net returns recorded from various intercropping systems remained at par with north-south and east-west row orientation. Spring maize + spring groundnut intercropping system recorded significant higher growth and development parameters of spring maize and remained at par with spring maize + summer squash, sole spring maize and spring maize + maize (fodder) but significantly higher than spring maize + spinach. Spinach recorded highest value of aggressively (0.42) and gave maximum competition to spring maize. Spring maize equivalent yield, net returns, land equivalent ratio and area time equivalent ratio were significantly higher under spring maize + summer squash system as compared to all other systems. Spring maize + summer squash proved highly productive, profitable and viable intercropping system which gave 92.4% higher spring maize equivalent yield and ` 60200 ha-1 higher net returns in comparison to sole spring maize.